2015
DOI: 10.1186/s12955-015-0388-0
|View full text |Cite
|
Sign up to set email alerts
|

Disease profile and health-related quality of life (HRQoL) using the EuroQol (EQ-5D + C) questionnaire for chronic metallic mercury vapor intoxication

Abstract: BackgroundToxic mercury is still being used today for example by workers mining gold, resulting in diverse health symptoms in users and individuals in proximity. A considerable burden of disease (BoD) can be assumed, while previous analyses were limited by data scarcity. Besides limited epidemiological data, neither data about the health-related quality of life (HRQoL) nor about the disease severity (disability weight, DW) is available. The aim of the project was to develop disease profiles of chronic metallic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Four participants of this study, one having CMI (Additional files 4 and 7) reported a health state, which is the same or worse than the health state for a moderate (121222) form of chronic metallic mercury vapor intoxication assessed by expert interviews [22]. This could mean, that experts focus on the disease and its health limitations and therefore rate a health condition worse than the affected people would rate it [42].…”
Section: Health Related Quality Of Life (Hrqol)mentioning
confidence: 95%
See 2 more Smart Citations
“…Four participants of this study, one having CMI (Additional files 4 and 7) reported a health state, which is the same or worse than the health state for a moderate (121222) form of chronic metallic mercury vapor intoxication assessed by expert interviews [22]. This could mean, that experts focus on the disease and its health limitations and therefore rate a health condition worse than the affected people would rate it [42].…”
Section: Health Related Quality Of Life (Hrqol)mentioning
confidence: 95%
“…This could mean, that experts focus on the disease and its health limitations and therefore rate a health condition worse than the affected people would rate it [42]. None of the participants stated a health state which corresponds to the health state for a severe (233333) form of chronic metallic mercury vapor intoxication [22]. It is assumable, that people suffering from the most severe form of this intoxication are no longer able to work [15] or to participate in such a study like this.…”
Section: Health Related Quality Of Life (Hrqol)mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the DW of a moderate CMMVI, a different DW for severe CMMVI is available. 21 However, the available data do not allow a stratified estimate on the prevalence distinguishing between moderate and severe cases. Because of its severe effects on the human body, such as severe coordination problems and difficulties in concentrating, and its restrictions on the quality of life, such as not being able to perform usual activities, 21 it is likely that this health condition would restrict mining work.…”
Section: R E S U L T Smentioning
confidence: 99%
“…Recently, DWs for chronic mercury intoxication as a result of metallic mercury vapor were derived to improve the input data for DALY quantifications. 20 The DWs were based on detailed case descriptions of moderate and severe chronic metallic mercury vapor intoxication (CMMVI), 21 which is assumed to be the main health outcome resulting from exposure to mercury in ASGM.…”
Section: Introductionmentioning
confidence: 99%